PREVENTION OF PRESSURE ULCERS: EVALUATION OF NURSING PROFESSIONALS' KNOWLEDGE - Layrianne Emmanuely Silva Rocha; Edna de Freitas Gomes Ruas; Jaciara Aparecida Dias Santos; Cássio de Almeida Lima; Jair Almeida Carneiro; Fernanda Marques da Costa (Universidade Federal do Paraná, 2015)
The aim was to assess the nursing team's knowledge regarding measures for preventing pressure ulcers in adults and older adults. The research was descriptive-exploratory with a quantitative approach. A structured questionnaire was used, based on the Pieper Pressure Ulcer Knowledge test. Data collection took place in October - December 2013. The descriptive and bivariate analysis of the data was undertaken with the support of the Statistical Package for the Social Sciences software, version 18.0. Among the 85 professionals, the global mean of the test applied was 84.21% for the nurses, and 68.42% for the nursing technicians. Only 22% of the nurses obtained correct answers for more than 90% of the test on their knowledge, and only 12% of the technicians reached this level. There was a statistically significant difference between greater length of service, greater age and professional category, indicating greater knowledge, above all on the part of the nurses in certain aspects. There is a shortage of knowledge, requiring constant and effective educational interventions so as to improve the care provided.